Pengendalian Kualitas dengan Pendekatan Six Sigma dan New Seventools sebagai Upaya Perbaikan Produk - Suhartini; Mochammad Basjir; Arief Tri Hariyono (2477 - 6165, 2020)
X is a manufacturing company engaged in galvalume processing. Hollow Galvalume is a leading product of CV. X. In each production process, there was product failure or defective products. If defective products occurred frequently, it could harm the company. Therefore, the objectives of study were to identify and analyse the causes of product defects and provide recommendations for improvements to minimize defective products. The methods used were Six Sigma and New Seventools. The Six Sigma method has 5 stages, namely Define, Measure, Analyse, Improve, and Control. The results of the calculation showed value of Defect per Million Opportunity was 14721 and sigma value of 3.69. Thus, the production of hollow products reached the Indonesian average industrial level, but the company wants to make improvements continuously. The results of improvement stage using New Seventools provided recommendations for improvements, among others, training for workers to understand work procedures better, regular schedule of machine maintenance, material inspection process monitoring, making a list of materials planned to be used, addition of special area and facilities for material warehouse.